SOCIAL CAPITAL AND ITS IMPACT ON FOOD SECURITY IN INDONESIA - Octananda, Adi Sofiyan; Wisana, I Dewa Gede Karma (Ekonomi Bisnis, 2024)
This study examines the impact of social capital on food security in Indonesia using Indonesian Family Life Survey (IFLS5) data. In previous studies, the impact of social capital on food security did not consider the endogeneity of social capital. This study uses two-stage least squares (2SLS) and conditional mixed process (CMP) estimation methods using trust in villages as instruments to estimate social capital and examine its impact on food security as measured by food consumption scores and food consumption groups. The results show that social capital positively affects food security, as measured by food consumption scores and food consumption groups.